Innovative development of the farming sector in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
The main sphere of agriculture – farming– receives inputs from 80 in dustries and sells its products in more than 60 industries. Innovative devel opment of agriculture is its qualitative transformation achieved due to the growth of the productive forces while improving organizational-economic mechanism of agriculture and industries which interact with it. It provides an ever-expanding use of more advanced technologies of production and processing of agricultural products, improved crop varieties and animal breeds, new machines, progressive organizational and economic models of modern information technologies and other innovations.The dynamic development of agriculture – a decisive condition not only to build and improve the quality of food resources, but also the progressive develop ment of the economy.
Keywords: Agriculture; Farming; Innovation; Technology of Foresight